EFFICACY OF TWO APPROACHES OF TRANSFORAMINAL EPIDURAL INJECTIONS IN PATIENTS OF LUMBAR RADICULOPATHY - Ali, Moazzam; Iqbal, Rashid; Waseem, Majid; Ali, Liaquat; Talib, Tahseen; Khawar, Maliha (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the efficacy of transforaminal epidural steroid injection (TFESI) using conventional versus Kambin’s triangle approaches in patients of lumbar radiculopathy.Study Design: Quasi experimental study.Place and Duration of Study: Department of Pain Medicine, Combined Military Hospital Rawalpindi Pakistan, from Oct 2019 to Apr 2020.Methodology: Eighty patients suffering from lumbar radiculopathy fulfilling the inclusion criteria were included in this study and were randomly assigned to undergo transforaminal epidural steroid injection using either conventional approach (group C) or the Kambin’s triangle (group K) approach. Pain scores and patient satisfaction levels were recorded at 4 and 8 weeks after the procedure.Results: In both groups, the pain score (group C pre-procedure NRS =7.28 ± 1.26 vs post-procedure NRS = 2.14 ± 0.81, group K pre-procedure NRS = 7.33 ± 1.16 vs post-procedure NRS=2.70 ± 0.94) and patient satisfaction improved 4 and 8 weeks after the procedure. The pain score (p-value=0.21) and patient satisfaction score (p-value=0.88) however were not significantly different between groups.Conclusion: This study demonstrated that using conventional or Kambin’s approach exhibits no difference in decreasing pain score or patient satisfaction level.